2018
DOI: 10.3102/0002831218808219
|View full text |Cite
|
Sign up to set email alerts
|

Under What Conditions Do School Districts Learn From External Partners? The Role of Absorptive Capacity

Abstract: School district central offices regularly engage with external partners in improvement efforts, but these partnerships are not always productive. Indeed, little is known about under what conditions partnerships are likely to lead to organizational learning outcomes. We conducted a longitudinal comparative case study of two departments in one urban school district central office, both working with the same external partner. Data included 131 interviews and 372 hours of observations as well as artifacts and soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 76 publications
1
54
0
1
Order By: Relevance
“…The potential impact of such strategies for others adopting them is of course important, but so is an assessment of their utility and perceived value to stakeholder groups. Also, potentially important are ideas or concepts produced by partnerships, which can move from projects into systems in ways that shift how people think about an issue, with consequences for policies (Farrell et al, 2019). Or, experiences within a research collaboration may create opportunities for participants to take on new methods of inquiry in their day-to-day lives, so that they could see themselves as knowledge producers (Cammarota & Fine, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The potential impact of such strategies for others adopting them is of course important, but so is an assessment of their utility and perceived value to stakeholder groups. Also, potentially important are ideas or concepts produced by partnerships, which can move from projects into systems in ways that shift how people think about an issue, with consequences for policies (Farrell et al, 2019). Or, experiences within a research collaboration may create opportunities for participants to take on new methods of inquiry in their day-to-day lives, so that they could see themselves as knowledge producers (Cammarota & Fine, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Our conceptual review and illustrative case examples provide key analytic points of the use of YPAR evidence. We identified conditions from the URE literature likely to enhance YPAR use: timely, valid, and easy-to-understand research that is locally relevant and action oriented; collegial communication channels between researchers and practitioners/policymakers; and decision-makers' and organizations' absorptive capacity to use research (Coburn, Tour e, & Yamashita, 2009;Dagenais et al, 2012;Farrell, Coburn, & Chong, 2019;Tseng & Nutley, 2014). The prior YPAR literature also suggested factors that might undermine the use of YPAR evidence, including insufficient follow-through and "traction" (Kirshner, 2007;Ozer et al, 2010), limited capacity for implementing YPAR (Ozer et al, 2008(Ozer et al, , 2010, and biases against youth .…”
Section: Discussionmentioning
confidence: 99%
“…Social networks strengthen the use of research evidence (Langer, Tripney, & Gough, 2016), particularly the role of effective "brokers" whose relationships span the boundaries between research and practice (Neal, Neal, Kornbluh, Mills, & Lawlor, 2015). Further, recent observational and interview research identified within-district differences in "absorptive capacity" for use of research evidence, based on departmental network structures (Farrell, Coburn, & Chong, 2019). We note that absorptive capacity in the URE literature refers to the ability to apply new evidence from outside of the district by integrating it into the organization's routines and practices, but to our knowledge the literature has not considered organizational ability or motivation to apply new evidence from students or other stakeholders within it.…”
Section: Use Of Research Evidence To Address Research-practice Gapsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to maintain a local system that creates innovations through inter-organisational learning, existing research on non-educational (Lewin et al, 2011) and educational organisations Farrell, Coburn, & Chong, 2018) has suggested that the ability to absorb external knowledge is a key factor for forming and sustaining effective organisational learning processes. In the case study, this theoretical point was embodied in the long-term partnerships with universities and research institutes paired with a systematic approach in practice to inter-municipality collaboration in workshops and networks that span municipality and departmental boundaries.…”
Section: Absorptive Capacitymentioning
confidence: 99%